Epidemiological Study of Tobacco Use Among Male Aged 15 Year and Above in Urban Area of Ghaziabad City (Up) - Pathak, Nitin Kumar; Pawaiya, Amit Singh; Jha, Ajay; Dixit, Anil (National Journal of Community Medicine, 2014)
Background: Tobacco use among children is becoming a serious problem in developing countries. Tobacco is the most easily legally available addictive substance which contributes significantly to premature death and long term suffering. This study is formulated with the objectives to study prevalence of tobacco habits among male age 15 year and above in urban area of Ghaziabad city (UP) Material and Method: A cross sectional study was conducted on 896 individuals aged ≥15 years by house to house visit, selected from urban field practice area of the Santosh medical college, Ghaziabad (U.P) by using Systematic random sampling between May 2010 to April 2011. Result: In the present study over all prevalence of tobacco use was 54.6 %( 26.5% for smokeless tobacco and 28.1% for smoking). The prevalence of tobacco abuse was more in nuclear families than joint families. The age wise trend of smoking was found to be 8.1% in 15-19 years age group, and gradually increased 18.3% in 40-49 years age group, while decreased to 10.0 % in more than 60 years age. Factors such as substance use by parents, unemployment and sibling pressure and peer pressure were significantly associated with substance use by study subjects. Conclusion: Tobacco addiction is emerging as a big threat among children. The study documented prevalence and predictors of tobacco use. The study population is at risk of tobacco use related morbidity and mortality and needs action targeting the most vulnerable population.